2015
DOI: 10.1007/s00586-015-4262-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of syringomyelia unrelated to Chiari malformation or spinal cord injury

Abstract: To remove the cause of syringomyelia, surgical planning will rely on thorough clinical history and accurate imaging to determine the site of cerebrospinal fluid obstruction. Craniocervical decompression to dissect basal arachnoiditis in the posterior fossa can be recommended in hindbrain syringomyelia. Treatment of non-hindbrain arachnoiditis is more controversial, probably owing to uncertainties about the extent of adhesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In our cohort, the foramen magnum area was first evaluated by comparing the preoperative and postoperative MRI findings for the first failed PFD, including the size of the cisterna magna and extent of decompression of cerebellar ptosis, pseudo meningocele formation, anterior compression of the odontoid, and/or craniocervical instability. Several researchers ( 8 , 10 , 30 ) have suggested that the upper segment of the syrinx near the foramen of magendie indicates underlying pathological changes in the foramen magnum area, which can be removed at the craniocervical level to restore free CSF flow.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, the foramen magnum area was first evaluated by comparing the preoperative and postoperative MRI findings for the first failed PFD, including the size of the cisterna magna and extent of decompression of cerebellar ptosis, pseudo meningocele formation, anterior compression of the odontoid, and/or craniocervical instability. Several researchers ( 8 , 10 , 30 ) have suggested that the upper segment of the syrinx near the foramen of magendie indicates underlying pathological changes in the foramen magnum area, which can be removed at the craniocervical level to restore free CSF flow.…”
Section: Discussionmentioning
confidence: 99%
“…When there is progression in the neurological deficit, definitive treatment is required. Craniovertebral decompression may result in improvement in neurological symptoms and signs 12,13. This is probably due to release of pressure and traction on cranial nerves.…”
Section: Discussionmentioning
confidence: 99%